SEMANTICS OF PERFUME AND COSMETIC NAMING IN THE SOCIAL STRATIFICATION ASPECT - Galytska, E. (Studia Philologica, 2019)
The article deals with the problem of English perfume and cosmetic naming. Special attention is given to the ways of social stratification verbalization. The system of indicators is responsible for the semantic reflecting social stratification explicitly. These indicators are connected with the social status or professional activity in a semantic way. The system of symbols-markers reflects social stratification implicitly. These symbols-markers are connected with object symbols or personal names. Object symbols are divided into toponymes and gemonymes. Personal name symbols are divided into real person names and mythonymes. Using the dictionary definitions of indicators and symbols-markers makes possible to identify archesemes, differential semes. These semes are basic criterium for further grasping the semantic bearers into corresponding groups and subgroups.